Minimum hydrogen consumption power allocation strategy for the multi-stack fuel cell (MFC) system based on a discrete approach - Liang, YiFan; Liang, QianChao; Zhao, JianFeng; He, JunNeng (Frontiers in Energy Research, 2022)
In high-powered application scenarios, a multi-stack fuel cell system (MFCS) could have advantages such as higher robustness, lifetime, and reliability than a single-stack fuel cell system. In particular, MFCS could maintain a high efficiency and increase system redundancy by power configuration between subsystems. In order to reduce the operational expenses for systems, a reasonable power management strategy is necessary to minimize the hydrogen consumption of MFCS. First, the power-hydrogen consumption curve of the single-stack fuel cell system is discretized from experimental measurements. Next, the discrete data are reassembled by the inverse derivation of the dynamic programming method to produce a minimum solution for the hydrogen consumption in the output power range. It is found that the strategy varies depending on activated state On or Off. Finally, two power allocation strategies are developed and modeled in a lookup-table block considering the activated state. The optimal stack output power strategy is analyzed with four stacks. The results indicate that the hydrogen consumption is smaller and more efficient than the other allocation strategies. It can respond to the load demand with a high efficiency sooner than the average strategy.